2021
DOI: 10.1002/qua.26666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vacancy defect on quantum capacitance, electronic and magnetic properties of Sc2CF2 monolayer

Abstract: Two-dimensional (2D) MXene materials have attracted much attention in recent years because of their excellent properties. In this paper, we theoretically investigated the quantum capacitance, electronic and optical properties of pristine Sc 2 CF 2 and the vacancy-doping Sc 2 CF 2 monolayers by first principles calculations. Pristine Sc 2 CF 2 is the most stable structure among the four investigated systems according to the analysis of binding energy, and the introduction of vacancy does not improve the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…71 Additionally, our results were compared with the work of Cui et al on Janus Sc 2 CF 2 , which showed a quantum capacitance of 34.09 mF cm À2 at positive bias. 72 Our findings underscored the competitive nature of our S/Se and S/Te Janus heterostructures regarding quantum capacitance values.…”
Section: Presents the Maximumsupporting
confidence: 54%
“…71 Additionally, our results were compared with the work of Cui et al on Janus Sc 2 CF 2 , which showed a quantum capacitance of 34.09 mF cm À2 at positive bias. 72 Our findings underscored the competitive nature of our S/Se and S/Te Janus heterostructures regarding quantum capacitance values.…”
Section: Presents the Maximumsupporting
confidence: 54%
“…Stanene is a novel material that has received increasing attention in recent years. It has been successfully realized by epitaxial growth on Bi 2 Te 3 (111) substrates [70][71][72]. Stanene exhibits several remarkable features, including large spin-orbit gaps, topological superconductivity, quantum anomalous Hall behavior, giant magnetoresistance, and efficient thermoelectricity [73].…”
Section: Stanenementioning
confidence: 99%
“…Their results show that the maximum CQ value of Hf2C is 549 µF/cm 2 (0.56 V). At positive bias, the CQ of the Subsequently, Cui et al theoretically studied the C Q of Sc 2 CF 2 with different atomic vacancies (Figure 4c) [111]. They observe that, at positive bias, pristine Sc 2 CF 2 has almost no C Q , while the introduction of vacancies increases it.…”
Section: Hfn+1cntxmentioning
confidence: 99%